ETIKA BISNIS DALAM PERSPEKTIF ALQURAN: MENGGALI NILAI IDEAL MORAL SEBAGAI UPAYA KONTEKSTUAL-UNIVERSAL - Desi Wahyuni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
Doing business without ethics will give birth to a generation of capitalists from both micro and macroeconomic systems. Therefore, ethics in the construct of the business world becomes something urgent to be considered. The focus of this research is trying to find the conception and moral ideal values in Islamic business ethics based on the spirit of the Qur'an and Hadits and by using the theory of Maqasid ash-Shatibi Syatibi which is based on two things namely ta'lil (legal determination based on illat), and al-mashalih wa al-mafasid (benefit and damage). This research has implications in business ethics that is with the changing times that continue to develop, the conception must always be used as a perspective or umbrella norm that must be held in the ethics of doing business. The conclusion of this study is the moral ideal value that must be held, namely: stay away from the nature of al-Ghisy, azh-Zhulm, and al-Gharar. These three variables are universal concepts that must always be considered, so any form and business model that is run must refer to and make these three variables as peptization and the main reference for realizing contextualization processes based on shari'a spirit in universal business ethics.